An optimal systematic sampling scheme - Khan, Z. (Taylor and Francis Ltd., 2020)
This paper aims to increase the efficiency of estimator through the optimal pairing of units in systematic sampling. The proposed Optimal Systematic Sampling Scheme is very simple, yet more generalized than any other systematic sampling scheme available in the literature. This scheme is applicable not only for the case where population size is multiple of sample size but also for other cases where this condition may not hold. Efficiency comparisons with the well-known sampling schemes have also been carried out both theoretically and numerically. Â© 2020, Â© 2020 Informa UK Limited, trading as Taylor & Francis Group.